Empowering UMKM of Woven Handicrafts Through Digital Marketing and Social Media in Pematang Buluh Village, Tanjung Jabung Barat Regency, Jambi Province: Pemberdayaan UMKM Kerajinan Anyaman Melalui Digital Marketing dan Media Sosial di Desa Pematang Buluh Kabupaten Tanjung Jabung Barat Provinsi Jambi - Ahmad Syukron Prasaja; Irma Sagala; Ema Risna Wati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Pematang Buluh Village, Betara district, Tanjung Jabung Barat Regency could develop and improve the community's economy with woven craft products. However, there are several problems in the development efforts of wicker handicrafts. The main problem is that the craftsmen only market their products manually (offline), thus hampering the market reach. The main objective of this service activity is to improve community welfare through the development of woven crafts. The result of this activity is that the Pematang Buluh Village community knows the importance and magnitude of the role of online marketing (digital marketing) in marketing woven purun and resam handicraft products. This knowledge is supported by training in creating marketing accounts and taking attractive product catalogs to attract buyers so that the craftsmen are ready to market and develop their business online.